Determinants of equity-based and co-operative foreign R&D and impact on the parent firm's performance - Martin Berger; Heinz Hollenstein (ETH Zurich, KOF Swiss Economic Institute, 2012)
The paper complements entry mode research by dealing with the choice of alternative modes of governance in the specific case of foreign R&D and its impact on a parent firm's performance. Firstly, we identify the factors that determine whether a firm locates abroad any R&D activities, and, if it does so, whether it chooses an equity-based rather than a non-equity co-operative mode of governance. The OLI paradigm is used as theoretical background of this analysis. Secondly, we determine the impact of foreign R&D on a parent firm's performance in terms of innovation output and labour productivity, and investigate whether this effect differs among firms using the one or the other governance mode. The study is based on separate estimations for Switzerland and Austria using comparable firm data and model specifications. The two countries are interesting cases as they strongly differ in terms of level and pattern of internationalisation.
Keywords: F23; L22; L24; O31; 330; Internationalisation of R&D; Governance of foreign R&D; International R&D cooperation; Foreign R&D and performance; OLI paradigm and R&D; Industrielle Forschung; Ausländische Tochtergesellschaft; Corporate Governance; Unternehmenswachstum; Vergleich; Schweiz; Österreich